Assessing Complexity Among Patients With Tuberculosis in California, 1993–2016. (4th July 2020) - Vaisman, Alon; Barry, Pennan; Flood, Jennifer
Abstract: Background: Although the number of patients with active tuberculosis (TB) has decreased in the last 25 years, anecdotal reports suggest that the complexity of these patients has increased. However, this complexity and its components have never been quantified or defined. We therefore aimed to describe the complexity of patients with active TB in California during 1993–2016. Methods: We analyzed data on patient comorbidities, clinical features, and demographics from the California Department of Public Health TB Registry. All adult patients who were alive at the time of TB diagnosis in California during 1993–2016 were included in the analyses. Factors deemed by an expert panel to increase complexity (ie, increased resources or expertise requirement for successful management) were analyzed and included the following: age >75 years, HIV infection, multidrug resistance (MDR), and extrapulmonary TB disease. Second, using additional information on other comorbidities available starting in 2010, we performed exploratory factor analysis on 25 variables in order to define the dimensions of complexity. Results: Among the 67 512 patients analyzed, the proportion of patients with extrapulmonary disease, age >75 years, or MDR-TB each increased over the study period ( P < .001), while the proportion of patients with HIV decreased. Furthermore, the proportion of patients with at least 1 factor of those increased, rising from 38.8% to 45.3% ( P < .001) from 1993 to 2016. Dimensions of complexity identified in the exploratory factor analysis included the following: race/immigration, social features, elderly/institutionalized, advanced TB, comorbidity, and drug resistance risk. Conclusions: In this first description of complexity in the setting of TB, we found that the complexity of patients with active TB has risen over the last 25 years in California. These findings suggest that despite the overall decline in active TB cases, effective management of more complex patients may require additional attention and resource investment.